PENINGKATAN HASIL BELAJAR MELALUI METODE DEMONSTRASI PADA MATA PELAJARAN IPA DI MI IRSYADULTHOLIBIN TUGU KABUPATEN TULUNGAGUNG - Sasmita, Adi (STKIP Al Islam Tunas Bangsa Bandar Lampung, 2019)
The purpose of this study was testing demonstration method in increasing students’ learning outcomes in science subjects in primary school MI Tugu.This research is a class action research which used sample of 20 students in the Class II MI Irsyadul Tholibin Tugu subdistrict Tulungagung regency. The research process is conducted through three cycles of the overall data were taken using observation and tests. The results showed that the use of appropriate methods of demonstration have a positive impact on learning. This proves the demonstration method in science learning can improve student learning outcomes. It is proved that the method of demonstration can improve student learning outcomes in learning in science subjects of class II MI Irsyadul Tholibin Tugu subdistrict Tulungagung regency in the academic year of 2014/2015.